Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a) |x - 5| - 2x = 3
| x - 5| = 3 + 2x
=> x - 5 = 3 + 2x hoặc x - 5 = -3 - 2x
=> -5 - 3 = 2x - x -5 + 3 = -2x - x
=> x = -8 -2 = -3x
=> x = 2/3
b) |2x - 1| + 3x = 1
|2x - 1| = 1 - 3x
=> 2x - 1 = 1 - 3x hoặc 2x - 1 = -1 + 3x
=> -1 - 1 = -3x - 2x -1 + 1 = 3x - 2x
=> -2 = -5x 0 = x
=> x = 2/5
c) | x - 5| = 3x - 2
=> x - 5 = 3x - 2 hoặc x - 5 = -3x + 2
=> -5 + 2 = 3x - x -5 - 2 = -3x - x
=> -3 = 2x -7 = -4x
=> x = -3/2 x = 7/4
d) |9 - 7x| = 5x - 3
=> 9 - 7x = 5x - 3 hoặc 9 - 7x = -5x + 3
=> 9 + 3 = 5x + 7x 9 - 3 = -5x + 7x
=> 12 = 12x 6 = 2x
=> x = 1 x = 3
Đăng ít một thôi bạn :v
a) 3x - (3 - 2x) = 0
3x - 3 + 2x = 0
5x - 3 = 0
5x = 0 + 3
5x = 3
x = 3/5
b) (x + 2).3 - 4x.3 = 0
3.(x + 2) - 12.x = 0
3[x + 2 - (4x)] = 0
x + 2 - 4 = 0
-3x + 2 = 0
-3x = 0 - 2
-3x = -2
x = 2/3
c) (x - 2)(x - 4)(1 - 7x) = 0
x - 2 = 0 hoặc x - 4 = 0 hoặc 1 - 7x = 0
x = 0 + 2 x = 0 + 4 -7x = 0 - 1
x = 2 x = 4 -7x = -1
x = 1/7
d) 4x2 - 1/4 = 0
4x2 = 0 + 1/4
4x2 = 1/4
x2 = 1/4 : 4
x2 = 1/16
x2 = (1/4)2
x = 1/4 hoặc x = -1/4
e) -3x2 + 48 = 0
3x2 - 48 = 0
3x2 = 0 + 48
3x2 = 48
x2 = 48 : 3
x2 = 16
x2 = 42
x = 4 hoặc x = -4
g) 3(1/2 - 1/3x)3 - 1/9 = 0
3(1/2 - x/3)3 - 1/9 = 0
3(1/2 - x/3)3 = 0 + 1/9
3(1/2 - x/3)3 = 1/9
(1/2 - x/3)3 = 1/9 : 3
(1/2 - x/3)3 = 1/27
(1/2 - x/3)3 = (1/3)3
1/2 - x/3 = 1/3
-x/3 = 1/3 - 1/2
-x/3 = -1/6
-x = -1/6.3
-x = -3/6 = -1/2
x = -1/2
m) 4x3 + 5x4 = 0
x3(4 + 5x) = 0
x = 0 hoặc 4 + 5x = 0
x = 0 5x = 0 - 4
5x = -4
x = -4/5
h) -x3 + 1/64x = 0
-x3 + x/64 = 0
x/64 - x3 = 0
x(1/64 - x3) = 0
x = 0 hoặc 1/64 - x2 = 0
x = 0 -x2 = 0 - 1/64
-x2 = -1/64
x2 = 1/64 = -+1/8
k) (x2 + 1)2 + 3x(x2 + 1) + 2 = 0
x4 + 2x2 + 1 + 3x3 + 3x + 2 = 0
x4 + 2x2 + 3 + 3x3 + 3x = 0
(x3 + 2x2 + 3)(x + 1) = 0
Mà x3 + 2x2 + 3 # 0 nên
x + 1 = 0
x = -1
a: \(\Leftrightarrow x\cdot\dfrac{2}{7}-\dfrac{3}{5}x=-1+\dfrac{1}{3}\)
\(\Leftrightarrow x\cdot\dfrac{-11}{35}=\dfrac{-2}{3}\)
hay x=70/33
b: \(\left|3x+7\right|-3x=7\)
\(\Leftrightarrow\left|3x+7\right|=3x+7\)
\(\Leftrightarrow3x+7\ge0\)
hay x>=-7/3
1.CMR:
a) 3.\(\left(x^2+y^2+z^2\right)-\left(x-y\right)^2\) \(-\left(y-z\right)^2-\left(z-x\right)^2=\left(x+y+z\right)^2\)